@GretaThunberg e: Ativismo Pelo Clima: A Representação Do Ativismo Digital No Twitter - Cavalcanti, Camilla Reisler (2024)
This thesis addresses the trajectory and impact of Greta Thunberg on climate activism, which began in 2018 with her solitary protest in front of the Swedish parliament and quickly made her one of the leading voices in this movement. Her engagement on social media provided a global reach for her messages on climate change, criticism of the inefficiency of leaders and defence of science, mobilising millions for environmental action. The study seeks to critically analyse the discursive representation of the social actor @GretaThunberg and her interaction with the digital macro-movement according to the theoretical frameworks proposed by van Dijk (2021). The methodological approach combines qualitative and quantitative techniques, including digital network analysis and Critical Studies of Multimodal Discourse, focusing on the activist's publications between 2021 and 2023 on the former Twitter (currently X). The massive data collection carried out by LABIC allowed a multidisciplinary analysis that revealed the positioning of the actors, the dominant perspectives and the terms prevalent in the discussions. The research integrates the digital network analysis, as proposed by Malini (2016), with Critical Studies of Multimodal Discourse, based on the contributions of Ledin and Machin (2018, 2020) and van Leeuwen (2008), as well as the previous works of van Dijk (1998, 2006, 2012a, 2012b, 2014). This multidisciplinary approach aims to identify discursive strategies that contribute to constructing a cohesive social positioning within the network. The theoretical foundation incorporates considerations about ideology, context and recontextualization, allowing a deeper analysis of the discursive boundary between "us" and "them". This theoretical integration broadens our understanding of the social dynamics of digital activism and provides valuable insights into the formation and evolution of online engagement networks. The decentralised nature of social networks and the constant interaction between users were fundamental to understanding how multiple voices come together and challenge narratives. According to Bakhtin (2011), the dialogical chain concept is relevant in this context, highlighting how each interaction contributes to recontextualizing the discourse in real-time. Data analysis revealed a discursive boundary between "activists" and "inactivists", with Greta Thunberg consolidating a "majority of minorities" by holding the hegemonic status quo accountable. However, the movement faces challenges from social justice issues and external events, such as pandemics and international conflicts, affecting its effectiveness and cohesion. The research seeks to shed light onto the evolution of public perception of climate activism and the influence of networked actors in society. Furthermore, it highlights the challenges activists face in the era of digital platforms, such as vulnerability to digital ephemerality and the polarisation of discussions. The results contribute to a deeper understanding of the social dynamics of digital activism and to the knowledge of the mechanisms and validity of digital social movements in contemporary times.